On Some Narrations in the (Post)Industrial Design Field - Możdżyński , Paweł (Załącznik Kulturoznawczy, 2014)
This text examines main narrations of the socio-cultural design field in the postindustrial period. The author starts from the creation of the definition of postindustriality. Next he explores main trends of contemporary design (DIY; eco/social design; design for all senses; design thinking, design for experience). Finally he tries to apply for the interpretation of this topic sociological categories of Jean Baudrillard and George Ritzer, eg.: ‘madness of production’, ‘immaterial consumption’, ‘hiperreality’, ‘simulacra’.